Simultaneous determination of major type‐B trichothecenes and the de‐epoxy metabolite of deoxynivalenol in chicken tissues by HPLC–MS/MS. Issue 6 (8th February 2014) - Xu, Lixiao; Zhang, Guijun; Guo, Chunna; Zhang, Yaping; Zhang, Yi; Zheng, Jianlong; Yang, Haicui; Yang, Dexue; He, Limin; Zeng, Zhenling; Fang, Binghu
<x xml:space="preserve">Abstract</x> In this study, a specific and sensitive LC–MS/MS method for the simultaneous analysis of type‐B trichothecenes (deoxynivalenol, 3‐acetyldeoxynivalenol, and 15‐acetyldeoxynivalenol) and the de‐epoxy metabolite of deoxynivalenol (de‐epoxy‐deoxynivalenol) in chicken muscle, liver, kidney, and fat tissues was developed and validated. The method involved an extraction step using ethyl acetate, followed by the evaporation of the supernatant, which was further purified by an Oasis HLB SPE cartridge (Waters, Milford, MA, USA). Chromatographic separation was performed on a C18 column by detection with MS in multiple‐reaction monitoring mode and using a gradient elution program with 0.1% formic acid in water and methanol. The correlation coefficients (r) for each calibration curve were >0.99 within the experimental concentration range. The extraction recoveries ranged from 73.7 to 106.4%, with intraday and interday RSD < 11.6% at three levels of concentrations of 2, 10, and 100 μg/kg. The decision limits and the detection capabilities of the analytes in the chicken tissues ranged from 0.16 to 0.92 and 0.68 to 2.07 μg/kg, respectively. The results demonstrated the applicability of this sensitive procedure to the determination of trichothecenes in chicken tissue samples.